Why is Social Justice Possible? Social Justice Issues during China$1 (Bs Period of Transition /s - Wu, Zhongmin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2024)
This is an open access book. This OA book contains extensive research on social justice during China$1 (Bs transition period. Rather than taking a macro-historical approach, or looking at social justice from a philosophical perspective, the book focuses on relevant theories and justice at a meso-level. It looks at the basis for social justice, and details the basic values and the basic standpoints when it comes to social justice. It differentiates between the concepts of justice, righteousness, fairness and equality. It then lays out three social justice rules (related to equal opportunities, distribution and social adjustment), and discusses the ideas of intergenerational justice and procedural justice. The book looks from a sociological point of view at social justice during China's period of transition. It focuses on how certain rules affect the social strata, and how they lead to discrimination, inequalities, liberty, equality, universal justice and/or differential justice. This book assesses improper pursuits of social justice in China. It also looks at how the ideas of liberty and equality have evolved, and some of the key problems over the last 70 years. This book also explains some of the more popular social topics that foster empirical discussions. Since the reform and opening-up era, China has made great achievements when it comes to social development. The country has made notable progress with social justice. There are more equal opportunities than ever before. Nevertheless, there remain worrying problems when it comes to the idea of justice. To some extent, these problems offset the achievements. In some form, the development processes have been somewhat misguided, and these have had a negative impact on Chinese society and how it functions and develops. Therefore, this book is of theoretical and practical significance when it comes to social justice research. Wu Zhongmin, born in 1959 in Qingdao, China, is a distinguished scholar holding the title of First-Class Professor at the National Philosophy and Social Sciences of China. He serves as a leading expert at the Expert Research Center of the Party School of the Central Committee of CPC and is also a member of the National Committee of the Chinese People's Political Consultative Conference (CPPCC). .s
1: An Overview of Social Justice -- 2: The Different Concepts of Justice, Righteousness, Fairness and Equality -- 3: Equal Opportunities Rules in Social Justice -- 4: Primary Distribution Rules in Social Justice -- 5: Social Adaptation Rules for Social Justice -- 6: Intergenerational Justice -- 7: Procedural Justice -- 8: Social Justice Rules in Social Stratification -- 9: Discrimination and Discriminations in China At Present -- 10: Liberty -- 11: Equality. 12: The Evolution of Liberty and Equality in China, as Well as Problems Over the Last 70 Years -- 13: The Improper Pursuit of Social Justice -- 14: Modern People Are Increasingly Inseparable from Social Justice -- 15: Social Cooperation Is Increasingly Inseparable from Social Justice -- 16: Universal Justice and Differential Justice.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Social justice; Social history; Social policy; China -- History; Social Justice; Social History; Social Policy; History of China